History & crime : a transdisciplinary approach - Kehoe, Thomas J.; Pfeifer, Jeffrey E. (Emerald advances in historical criminology, 2021)
Revealing the cross utility potential of multiple disciplines to advance knowledge in crime studies, History & Crime showcases new research into crime from across the interdisciplinary perspectives of early modern and modern history, criminology, forensic psychology, and legal studies. Authored by emerging and established scholars from the around the world, the contributions span youth crime, feminist criminology, historic penology and court practices, through to the insanity defence, police corruption, and models for post-conflict governance. The chapters present the breadth of the work currently being undertaken around the world in this ground-breaking field, linking the present to the historic. Through these diverse chapters, the editors illustrate the current scholarship already bridging the oft-asserted divide between history and the social sciences. It is argued that differences in language and methodology may have created a mirage of disciplinary division. The collection consequently offers a unique opportunity for advancing a new framework for trans-disciplinary discourse to allow new research to be more easily interpreted and integrated across traditional disciplinary boundaries. This framework will guide future contributions in everything from histories of crime to future-focused crime scholarship, and by allowing better comprehension, drive ground-breaking new knowledge.